Developmental cascades linking stress inoculation, arousal regulation, and resilience - Lyons, David M.; Parker, Karen J.; Katz, Maor; Schatzberg, Alan F. (Frontiers in Behavioral Neuroscience, 2009)
Stressful experiences that are challenging but not overwhelming appear to promote the development of arousal regulation and resilience. Variously described in studies of humans as inoculating, steeling, or toughening, the notion that coping with early life stress enhances arousal regulation and resilience is further supported by longitudinal studies of squirrel monkey development. Exposure to early life stress inoculation diminishes subsequent indications of anxiety, increases exploration of novel situations, and decreases stress-levels of cortisol compared to age-matched monkeys raised in undisturbed social groups. Stress inoculation also enhances prefrontal-dependent cognitive control of behavior and increases ventromedial prefrontal cortical volumes. Larger volumes do not reflect increased cortical thickness but instead represent surface area expansion of ventromedial prefrontal cortex. Expansion of ventromedial prefrontal cortex coincides with increased white matter myelination inferred from diffusion tensor magnetic resonance imaging. These findings suggest that early life stress inoculation triggers developmental cascades across multiple domains of adaptive functioning. Prefrontal myelination and cortical expansion induced by the process of coping with stress support broad and enduring trait-like transformations in cognitive, motivational, and emotional aspects of behavior. Implications for programs designed to promote resilience in humans are discussed.